Geographic patterns in range sizes and their drivers of endemic angiosperms in China - Wang, Yunyun; Lyu, Tong; Luo, Ao; Dimitrov, Dimitar; Wang, Zhiheng (Ecosphere, 2023)
Abstract Geographic range size of endemic species is the most important indicator of species' vulnerability to extinction and conservation prioritization, yet variation in range size among species and across space has been relatively understudied. We investigated the variations and geographic patterns of the range size of 9898 angiosperm species endemic to China and compared the effects of historical and contemporary climate and species' functional traits associated with dispersal ability (including growth form, fruit type, and sexual system) on range size variations. Our results revealed that narrow-ranged endemic species are clustered in Southwest China where angiosperm species' richness peaks. Winter temperature had the strongest and negative effect on the range size of narrow-ranged endemic species across space and species, while climate seasonality had the strongest and positive effect on the range size of wide-ranged endemic species. Both historical and contemporary climate have also influenced species range size indirectly via their effects on species' functional traits associated with dispersal ability. Range size of all endemic species, narrow-ranged and wide-ranged, showed little phylogenetic signal, suggesting that phylogenetic conservatism plays a minor role in range size variations. Our results show that the range size of angiosperm species endemic to China is driven by both extrinsic spatiotemporal environmental factors and intrinsic species' traits that allow species to cope with environmental change.
Keywords: biodiversity conservation; climate change; dispersal ability; geographical distribution; macro-evo-devo; narrow-ranged species